Social work in the heritage of humanity: life story of a Sewellina Social Worker-Chile - Meriño-Montero, Ignacio Antonio (Prospectiva. Revista de Trabajo Social e Intervención Social, 2025)
The qualitative research on Mrs. Magali explores her trajectory in the historical context of Rancagua and the Sewell mining camp. Key categories such as motivation, professional decisions, challenges faced, and significant projects are analyzed using life history and content analysis. The results reveal how their social work, especially in periods of reconceptualization, impacted the policies and practices of their time. Category analysis highlights his influence on social transformation and historical conflicts that shaped his professional approach, demonstrating his crucial role in the evolution of social work.